CBIO-18. G-QUADRUPLEX STABILIZATION TARGETS ATRX-DEFICIENT HIGH-GRADE GLIOMA VIA INDUCTION OF p53-INDEPENDENT APOPTOSIS. (9th November 2020) - Dharmaiah, Sharvari; Farooqi, Ahsan; Alvarez, Christian; Sharin, Vladislav; Irvin, David; Huse, Jason
Abstract: Gliomas are the most common primary malignant brain tumor in adults and mutational inactivation of histone chaperone ATRX is a critical molecular marker in the classification of high-grade glioma (HGG). ATRX loss occurs with concurrent mutations in TP53 and IDH1 /2, altering genome-wide accessibility of chromatin and inducing replication stress and DNA damage via accumulations of abnormal G-quadruplex (G4) DNA secondary structures. While G4 stabilizers in particular hold strong therapeutic promise, the genomic consequences and efficacy of this treatment are poorly understood. We previously showed that chemical stabilization of G4s in ATRX-deficient normal human astrocytes (NHAs) results in lethality due to induction of replication stress, but it is unknown what drives this lethality in ATRX-deficient patient-derived preclinical models. We therefore sought to evaluate the mechanisms that underlie cell death in ATRX- and p53-deficient preclinical in vitro models following G4 stabilization. We found that ATRX-deficient glioma stem cells (GSCs) demonstrated dose-dependent enhanced sensitivity to G4 stabilization, compared to ATRX-intact controls. Evaluation of cell death mechanisms following G4 stabilization revealed a significant increase in cleaved caspase 3 expression and no p21 expression in ATRX-deficient GSCs, suggesting p53-independent apoptotic activation. Cell cycle flow analysis demonstrated G2/M checkpoint arrest in ATRX-deficient GSCs upon G4 stabilization, suggesting that p53 is nonfunctional at the G1/S checkpoint. Our preliminary findings now suggest that p73, a functional and structural homologue of p53, is activated and drives apoptosis in these ATRX-deficient GSCs. Furthermore, ATRX-deficient GSCs demonstrated upregulated expression of both pATR/pChk1 and pATM/pChk2, indicating enhanced replication stress and DNA damage via double-stranded breaks, respectively. These findings indicate that G4 stabilizers could potentially synergize with ionizing radiation, the current standard of care, as both therapies are DNA-damaging. Taken together, this study elucidates mechanisms of cytotoxicity and efficacy of a novel therapeutic strategy in ATRX-deficient preclinical models.